Determining Seed Viability During Fruit Maturation to Improve Seed Production and Availability of New Citrus Rootstocks - de Carvalho, Deived Uilian; Boakye, Daniel A.; Gast, Tim; Leite Junior, Rui Pereira; Alferez, Fernando (Frontiers in Plant Science, 2021)
In recent years, the pressure for replanting and resetting huanglongbing (HLB or citrus greening) affected citrus groves has led to an inadequate seed supply for the most popular rootstock cultivars in the State of Florida, USA. Early fruit harvesting of citrus rootstock might reduce fruit losses that impact seed availability, especially in HLB-endemic and hurricane hitting areas, if the physiological quality of the seeds is adequate. The effects of fruit maturity on seed quality and seedling performance of US-802, US-897 and US-942 citrus rootstocks were investigated for two consecutive growing seasons. The study included the evaluation of seed germination and nursery performance of the citrus rootstock seedlings. The germination test was performed in vitro, where seeds were hand-peeled, surface-sterilized and placed in culture tubes containing basal Murashige and Skoog medium. For the emergence test, seeds were sown in seedling trays containing sterilized growing substrate in a greenhouse with controlled-environment conditions. US-942 seeds had the best germination and emergence potential among the tested rootstocks. This rootstock also had the highest root and shoot growth rate, with high germination speed index and high multiple seedlings per seed. These results showed that US-942 seeds have vigorous germination, which may result in vigorous scion growth and rapid establishment in the field. Assays on fruit abscission response showed that by August, fruit is responsive to ethylene, and abscise, suggesting the seed was mature enough. This was confirmed by germination studies. Taken together, our findings indicate that fruits from US-897 and US-942 rootstocks can be harvested as early as August in contrast to the current procedures without losing germination potential. This will result in an increase in available seeds for nurseries in Florida.